CompTIA Security+ (SY0-601) Cert Prep: 5 Physical Security Design and Implementation. - Chapple, Mike (linkedin.com, 2020)
Prepare to take version SY0-601 of the CompTIA Security+ exam. Explore the details of the physical security design and implementation elements of the test.